Pendampingan Penerapan Desain Kemasan Sebagai Strategi Pemasaran Produk UMKM D’Klotiq Klompen Batik Etniq - Myrtanti, Reiny Ditta; Andjarsari, Sanny; Septiari, Renny (Universitas Muhammadiyah Mataram, 2026)
Abstract: This community service activity aims to improve the quality of the packaging of D'Klotiq Klompen Batik Etniq UMKM products through mentoring the implementation of more informative, attractive packaging designs that are in accordance with the characteristics of klompen as a traditional product. The main problem faced by partners is the use of simple packaging without brand identity and limited understanding of graphic design, branding and packaging material selection. The implementation method consists of three stages, namely observation and needs analysis, concept design, and implementation. The observation stage is carried out through interviews and surveys of the production process, as well as identifying the initial conditions of the packaging. The design stage focuses on creating alternative logo and packaging designs which are then discussed and revised with partners. Implementation is carried out by presenting packaging prototypes as applicable examples for UMKM. The results of the activity show that UMKM obtain a visual identity in the form of a new logo and a more representative and functional packaging design, which emphasizes wood and batik elements as the characteristics of klompen. The resulting design is expected to be able to increase the added value of the product, strengthen branding and increase consumer appeal, thus potentially increasing the competitiveness of UMKM in the local and national markets.Abstrak: Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan kualitas kemasan produk UMKM D’Klotiq Klompen Batik Etniq melalui pendampingan penerapan desain kemasan yang lebih informatif, menarik dan sesuai dengan karakteristik klompen sebagai produk tradisional. Permasalahan utama mitra adalah penggunaan kemasan sederhana tanpa identitas merek serta keterbatasan pemahaman mengenai desain grafis, branding dan pemilihan material kemasan. Metode pelaksanaan terdiri dari tiga tahap, yaitu observasi dan analisis kebutuhan, perancangan konsep, dan implementasi. Tahap observasi dilakukan melalui wawancara dan survei proses produksi, serta mengidentifikasi kondisi awal kemasan. Tahap perancangan berfokus pada pembuatan alternatif desain logo dan kemasan yang kemudian didiskusikan dan direvisi Bersama mitra. Implementasi dilakukan dengan penyajian prototipe kemasan sebagai contoh aplikatif bagi UMKM. Hasil kegiatan menunjukkan bahwa UMKM memperoleh identitas visual berupa logo baru serta desain kemasan yang lebih representatif dan fungsional, yang menonjolkan unsur kayu dan batik sebagai ciri khas klompen. Desain yang dihasilkan diharapkan mampu meningkatkan nilai tambah produk, memperkuat branding dan meningkatkan daya tarik konsumen, sehingga berpotensi meningkatkan daya saing UMKM di pasar local maupun nasional.